STRUCTURAL VERIFICATION, MOLECULAR DOCKING AND ANTIPROLIFERATIVE ACTIVITY FOR AMINO ACETYLENIC OXY QUINOXALINES: Pharmaceutical Science-Medicinal Chemistry - A MUHI-ELDEEN, ZUHAIR; S MUSTAFA, BAKR; ELHAM N AL-KAISSI; A GHATTAS, MOHAMMAD (International Journal of Life Science and Pharma Research, 2019)
Tyrosine kinase inhibitors of the epidermal growth factor receptor (EGFR) are of interest to drug companies. These proteins kinase (PKs) are considered as validated drug targets. In cancer, proteins kinases play a key role in regulating numerous cellular functions including increased proliferation, decreased apoptosis, increased invasion, metastasis, and promote angiogenesis. Tyrosine kinase overproduction inhibits the activity of various anticancer agents via suppression of key apoptotic mechanisms thereby leading to the development of cellular drug resistance. Targeting and inhibiting these kinases enzymes became attractive candidates for cancer therapy. The targeting of human epidermal growth factor receptor 2 (HER2 or ErB-2/neu) and epidermal growth factor receptor (EGFR or HER1/ErB1) by tyrosine kinase inhibitors (TKIs) represent a promising therapeutic approach in cancer therapy. The new novel 2- [4-(t-amino-1-yl)but-2-yn1-yl]quinoxaline (ZB-2 to ZB-8), provide effective overlap with (EGFR or HER2) through ionic, hydrogen bonding, charge transfer and hydrophobicity. The introduction of different basic amino moiety with acetylenic group in signal transduction inhibitor represents a novel and new approach in the management and treatment of cancer. These speculations were supported by molecular docking and pharmacological activity which shows an effective overlap with EGFR to initiate the inhibition activity leading to cancer treatment.